Análisis, diseño, desarrollo e implementación de un gestor de transporte automotriz para la Superintendencia de Control del Poder de Mercado - Pilicita Garrido, Fabricio Xavier (2016)
The web application that was developed to meet the need arises automation processes search the Superintendencia de Control del Poder del Mercado(SCPM) within the scope of vehicle management creating a web Transportation Management system that is responsible for managing information concerning vehicles belonging to the institution or individuals entering the premises of the same. It will also allow management applications to mobilize that will be created by employees of the superintendency. The portal administrator is responsible for assigning requests to authorize a vehicle and a driver or deny as it deems appropriate. The document is divided into 3 chapters which are detailed below. Chapter one presents reference to the Superintendencia de Control del Poder del Mercado information, why it was created and objectives. Besides the theoretical framework that contains the necessary concepts for building the software solution it is presented. Chapter two presents the analysis and design of the system. It focuses on defining customer requirements and create the solution using a software design methodology with their respective diagrams. Chapter three presents the tools used to build the application and testing to ensure the proper functioning of the software solution, to finish with the conclusions and recommendations obtained from the work done.